1989
DOI: 10.1080/00380768.1989.10434770
|View full text |Cite
|
Sign up to set email alerts
|

Apparent recovery of fertilizer n by vegetable crops

Abstract: Apparent recoveries of fertilizer N by crops were studied as their treatment in simulation models is a serious problem. Multi-level N fertilizer experiments in which fertilizer was broadcast and incorporated in soil immediately before drilling were carried out on a range of vegetable crops on adjacent sites of the same field. At final harvest, apparent recovery always declined approximately linearly with the increase in fertilizer N even when less was applied than was needed for maximum uptake; this contrasts … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 16 publications
3
41
1
Order By: Relevance
“…The two recovery factors are required because soil nitrogen and fertiliser nitrogen may be differently available in time and space. However, the author concluded that in most cases the two recovery factors can be considered nearly equivalent; therefore the uptake efficiency of fertiliser nitrogen (apparent nitrogen recovery) can be estimated on the basis of the nitrogen uptake of the unfertilised control as proposed by other authors (Greenwood et al, 1989;Zemenchik, Albrecht, 2002;Benincasa et al, 2011;Murphy et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The two recovery factors are required because soil nitrogen and fertiliser nitrogen may be differently available in time and space. However, the author concluded that in most cases the two recovery factors can be considered nearly equivalent; therefore the uptake efficiency of fertiliser nitrogen (apparent nitrogen recovery) can be estimated on the basis of the nitrogen uptake of the unfertilised control as proposed by other authors (Greenwood et al, 1989;Zemenchik, Albrecht, 2002;Benincasa et al, 2011;Murphy et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…Here the general assumption is -crops equally use the same amount of nitrogen despite the external sources (fertilisers) is available or not. Regardless of facts that more mobile forms of nutrients supplied by fertilisers could be used more efficiency if present compared with soil sources this approach of plant nutrient recovery calculation is widespread (Greenwood et al, 1989;Zemenchik, Albrecht, 2002;Brentrup, Palliere, 2010;Benincasa et al, 2011;Murphy et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The total grain yield was calculated according to the following formula: Total grain yield (tons/ha) = grain weight(g)/m2 / 100 [6]. Nitrogen use efficiency calculated as follows: NUE = grain yield/ actual amount of nitrogen added [7]. Seeds crude protein and crude fibre contents were determined following the standard methods of the Association of Official American Analytical Chemists [8].…”
Section: Methodsmentioning
confidence: 99%
“…The plateau level clearly is the consequence of the saturated sink capacity of the cauliflower crop. Greenwood et al (1989) compared the N response of vegetable and gramineous crops and found a linear response-plateau response more typical for gramineous than for vegetable crops where quadratic response function gave a better fit to the data. He interpreted this as the consequence of a restricted N availability especially during early growth stages of vegetable crops, where rooting density is much lower than for gramineous crops.…”
Section: H K a G E C A L T A N D H S T ü T Z E Lmentioning
confidence: 99%